How Does the Store Feel? Investigating the Mediating Effect of Emotion on Sensory Marketing and Consumer Behaviour - Ahmad Syamsudin (Shirkah: Journal of Economics and Business, 2025)
Amidst a highly competitive retail landscape, sensory marketing strategies have become crucial for fostering a positive store atmosphere through sensory stimuli. However, research examining how such stimuli evoke emotional responses to drive purchases remains limited, particularly within the context of minimarkets in an urban city like Palangkaraya, Indonesia, representing a significant research gap. This study aims to analyze the influence of sensory marketing on the purchase decisions of Alfamart consumers in the city of Palangkaraya, examining the crucial role of the emotional dimension as an intervening variable. Employing a quantitative survey design, data were collected from a sample of 75 Alfamart consumers via a structured questionnaire and were subsequently analyzed using Path Analysis. The results reveal that sensory marketing has a positive and significant influence on the consumer's emotional dimension. Subsequently, the emotional dimension proves to be a strong driver, exerting a positive and significant effect on purchase decisions. A key finding confirms that the emotional dimension fully mediates the relationship between sensory marketing and purchase decisions, indicating that in-store sensory experiences are translated into purchasing actions through the creation of specific feelings and moods. This study offers strategic guidance for Alfamart managers on optimizing sensory elements to foster stronger emotional bonds with consumers. It also enriches the marketing literature by elucidating the psychological mechanisms underlying the effectiveness of experiential marketing in the retail sector.